Gestão da informação em áreas de proteção ambiental: estudo de caso sobre a gestão do IDEFLOR-BIO na Apa mosaico do lago de Tucuruí - ALMEIDA, José Adilson Pinheiro (Universidade Federal do Pará, 2024)
A study of Information Management from a strategic perspective within the scope of Public Administration at the Tucuruí Lake Environmental Protection Area Conservation Unit, based on elements of the external and internal organizational environment, connected to Strategic Information Management and Strategic Intelligence, the research problem incorporates the following question: How can information management contribute to developing Strategic Intelligence about the Tucuruí Lake Environmental Protection Area in Pará State? With the general objective of analyzing the Information Management process as a determining factor for the development of Strategic Intelligence for the public environmental management of the Tucuruí Lake Conservation Unit in Pará State. Specific Objectives: a) map the information management process within the scope of public environmental management at conservation units; b) identify strategic factors influencing the internal and external environments of the Forest and Biodiversity Development Institute; c) verify the available resources applied to data and information management at the Forest and Biodiversity Development Institute related to the environmental conservation of the Tucuruí Lake Unit Monitoring System d) Analyze the potential of Strategic Intelligence, in order to ensure greater efficiency in public environmental management at the Forest and Biodiversity Development Institute, focused on the Tucuruí Lake Conservation Unit in Pará State. This research is characterized as exploratory and descriptive, with a qualitative and quantitative approach, as a case study of the Environment Protection Area of Tucuruí Lake in Pará State. A bibliographic survey and field research were undertaken, using systematic observation to capture data on the operational routine of the Institute and the physical structure of its work, as well as semi-structured interviews with the technicians of the Forestry and Biodiversity Development Institute of the Tucuruí Lake Conservation Unit, focusing on information gathering, storage, processing and dissemination activities. Based on field surveys, it was possible to demonstrate that Strategic Information Management, through mapping and ordering the flow of information, enhances the construction of Strategic Intelligence in a Conservation Unit, qualifying decision-making and the production of public policies on the environment. Finally, it was concluded that Information Science has many possibilities to collaborate with the preservation of the environment and sustainability through Information Management, generating efficiency, efficacy and effectiveness of public policies and management actions capable of producing inferences that direct public and private managers to more assertive decisions.